Composite nonlinear feedback control with multi-objective particle swarm optimization for active front steering system - Ramli L.; Sam Y.M.; Mohamed Z.; Khairi Aripin M.; Fahezal Ismail M. (Penerbit UTM Press, 2024)
Indexed by SCOPUS